Chromium(III) based Ziegler-Natta catalysts for olefin polymerization - Wong .J.X,; Gan .S.N,; Aishah .M.J, (Universiti Kebangsaan Malaysia, 2011)
Four chromium based oxo-trinuclear carboxylate complexes were prepared by reacting chromium(III) nitrate nonahydrate with acetic acid and substituted carboxylic acids. They were characterized using infrared spectroscopy (FT-IR). Chromium content of the complexes was determined by titrimetry method. The chromium(III) monochloroacetate complex, [Cr3O(ClCH2COO)6.3H2O]NO3.3H2O in combination with diethylaluminium chloride formed heterogeneous catalyst system for ethylene polymerization. Both Al/Cr ratio and temperature influenced the catalytic activity. The maximum activity was 1768 gPE/gCr/hr/atm, achieved by polymerizing at 29°C and monomer pressure around 1 atm, with Al/Cr ratio 30.8. Effect of chloro-substituent groups on carboxylic ligand was studied by comparing the catalytic acitivities of chromium(III) monochloroacetate, chromium(III) dichloroacetate, chromium(III) trichloroacetate and chromium(III) acetate.The polymerization reaction was found to be first order with respect to the monomer during the initial stage. The activity decreases very rapidly presumably due to fast decay of the active sites. The polyethylene was characterized using FT-IR and DSC, and the results showed that it was of high density and crystallinity.